IMPLEMENTASI METODE RUP (RATIONAL UNIFIED PROCESS) DALAM PEMBUATAN APLIKASI KASIR PADA TOKO AGUNG SAFETY GLASS - Zikri, Afdal; Mahfuzhi, AR.Walad; Marhalim, Marhalim; Imanullah, muhammad (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2026)
The rapid development of information technology encourages business actors to utilize computer-based systems to improve operational effectiveness and efficiency. Agung Safety Glass Shop, which is engaged in the sale of car glass, spare parts, variations, and vehicle repair services, previously still used a manual system in recording transactions, managing stock, and preparing sales reports, which often resulted in recording errors, difficulty monitoring inventory, delays in report preparation, and less than optimal service to customers. This study aims to implement the Rational Unified Process (RUP) method in developing a cashier application so that the system development process can be carried out in a structured and systematic manner according to user needs. The RUP method used includes four stages, namely Inception, Elaboration, Construction, and Transition, while the system design is modeled using the Unified Modeling Language (UML) which includes Use Case Diagrams, Activity Diagrams, Sequence Diagrams, and Entity Relationship Diagrams (ERD) to clearly describe the process flow and data structure. The research methods include literature studies, observations, interviews, needs analysis, design, development, and system testing. The research results show that the developed cashier application is capable of managing product data, processing transactions with automatic total and change calculations, updating stock in real-time, printing receipts, and generating reports that can be exported to Excel format. Testing using the Black Box Testing method proved that all features work according to user needs, so that the implementation of this application makes the transaction process faster, more accurate, and more efficient and helps shop owners in making business decisions.